Beneficial effects of baicalein on a model of allergic rhinitis - Liu Tao; Xu Jing; Wu Yungang; Li Xiaoxia; Ding Detao; Ma Dengdian; Yao Mengwei; Wei Wenzhong; Zhang Wei; Wang Shaohua; Yao Jing; Li Xiaoyu (Acta Pharmaceutica)
Allergic rhinitis (AR) is a common disease that causes severe inflammation and even disabilities. Previous studies have reported baicalein to have an anti-inflammatory effect. However, the pharmacological action of baicalein on anaphylaxis has not been clarified yet. This study assessed the in vivo protective effect of baicalein post-treatment in an ameliorating ovalbumin (OVA)-sensitized AR rat model. Baicalein attenuated histological alterations, aberrant tissue repair and inflammation after OVA-induced AR. Baicalein reduced the frequency of nasal/ear rubs and sneezes in rats, and inhibited generation of several inflammatory cytokines (TNF-α, IL-1β, and IL-6) in both blood and nasal lavage of rats. Infiltrations of eosinophils, lymphocyte, and neutrophils were decreased in baicalein-administered rats. Furthermore, baicalein inhibited the expression of STAT3 phosphorylation in the nasal mucosa. In summary, baicalein attenuated OVA-induced AR and inflammation, which suggests it as a promising therapeutic agent for the alleviation of AR-associated inflammation and pathology.